Positive electrode active material, positive electrode containing the same, and lithium secondary battery

JP7632945B2Active Publication Date: 2025-02-19LG CHEM LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023519756
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-01-08
Filing Date
2022-01-10
Publication Date
2025-02-19
Estimated Expiration
2042-01-10

AI Technical Summary

Benefits of technology

【0023】 本発明の正極活物質は、結晶粒の長軸配向性が高く、c軸配向性が低い結晶粒を特定の割合で含み、二次電池に適用する際に、優れた容量特性及びガス発生低減特性を具現することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007632945000011
    Figure 0007632945000011
  • Figure 0007632945000012
    Figure 0007632945000012
  • Figure 0007632945000013
    Figure 0007632945000013
Patent Text Reader

Abstract

The present invention relates to a positive electrode active material in which the degree of crystal grain long axis orientation DoA is 0.5 to 1, and the proportion of crystal grains C having a degree of crystal grain c-axis orientation of less than 0.5, represented by the cross product of the c-axis rotation vector Rc of the crystal lattice of the crystal grains and the position unit vector P' of the crystal grains obtained by electron backscatter diffraction (EBSD) analysis, is 25% to 70% of all crystal grains in the cross section of the positive electrode active material particle, as well as a positive electrode and a lithium secondary battery containing the same.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] [CROSS REFERENCE TO RELATED APPLICATIONS] This application claims the benefit of priority based on Korean Patent Application No. 10-2021-0002838, filed on January 8, 2021, and all contents disclosed in the documents of that Korean patent application are incorporated herein by reference.

[0002] The present invention relates to a positive electrode active material, a positive electrode including the same, and a lithium secondary battery, and more particularly, to an excellent positive electrode active material for a lithium secondary battery that, when applied to a secondary battery, can not only improve the capacity characteristics of the secondary battery but also reduce the amount of gas generated during charging and discharging of the secondary battery, and a positive electrode and a lithium secondary battery including the same. [Background technology]

[0003] In recent years, with the technological development and increasing demand for mobile devices and electric vehicles, the demand for secondary batteries as energy sources has been rapidly increasing. Among such secondary batteries, lithium secondary batteries, which have high energy density and voltage, long cycle life, and low self-discharge rate, have been commercialized and are widely used.

[0004] As the positive electrode active material for lithium secondary batteries, lithium transition metal oxides such as lithium cobalt oxides such as LiCoO2, lithium nickel oxides such as LiNiO2, lithium manganese oxides such as LiMnO2 or LiMn2O4, and lithium iron phosphate oxides such as LiFePO4 have been developed. a Co b Mn c ]O2, Li[Ni a Co b Al c ]O2, Li[Ni a Co b Mn c Al d Lithium composite transition metal oxides containing two or more transition metals, such as ]O2, have been developed and are widely used.

[0005] Lithium composite transition metal oxides containing two or more transition metals that have been developed so far are usually manufactured in the form of spherical secondary particles formed by agglomeration of tens to hundreds of primary particles, and physical properties such as lithium ion mobility and electrolyte impregnation ability vary depending on the orientation form and shape (aspect ratio) of the primary particles. Therefore, research is being conducted to improve the performance of positive electrode active materials by controlling the particle structure of the positive electrode active material particles.

[0006] Korean Patent No. 10-1611784 (Patent Document 1) discloses a positive electrode active material in which the length of the a-axis direction of the primary particles is longer than the length of the c-axis direction, and the a-axes of the primary particles are radially arranged. In Patent Document 1, the morphology and orientation of the primary particles of the positive electrode active material were analyzed using a scanning electron microscope (SEM) and / or a transmission electron microscope (TEM).

[0007] However, the TEM analysis used in Patent Document 1 has a problem in that it is difficult to represent the characteristics of the entire positive electrode active material particle because it only obtains information on a partial region, not on the entire particle. In addition, the physical properties of the positive electrode active material vary depending on the morphology and orientation of the primary particles as well as the morphology and orientation of the crystallines, so that even if the morphology and orientation of the primary particles are similar, different physical properties can be exhibited.

[0008] Therefore, in order to develop a positive electrode active material having better properties, research into the crystal grain structure of the positive electrode active material is required. [Prior art documents] [Patent documents]

[0009] [Patent Document 1] Korean Patent No. 10-1611784 Summary of the Invention [Problem to be solved by the invention]

[0010] In order to solve the above problems, the present invention aims to provide a positive electrode active material that contains a specific ratio of crystal grains whose major axis and c-axis orientations satisfy specific conditions, and thereby can improve the capacity characteristics of a secondary battery when applied to the secondary battery, as well as reduce the amount of gas generated during charging and discharging the secondary battery.

[0011] Another object of the present invention is to provide a positive electrode and a lithium secondary battery containing the positive electrode active material according to the present invention. [Means for solving the problem]

[0012] According to an embodiment, the present invention provides a positive electrode active material for a lithium secondary battery, in which a degree of crystal grain long axis orientation DoA represented by the following [Equation 1] is 0.5 to 1, and the proportion of crystal grains C having a degree of crystal grain c-axis orientation of less than 0.5 represented by the cross product of a c-axis rotation vector Rc of a crystal lattice of a crystal grain and a position unit vector P' of the crystal grain obtained by Electron Backscatter Diffraction (EBSD) analysis is 25% to 70% of all crystal grains in a cross section of the positive electrode active material particle: [Formula 1]

number

[0013] In this case, the scanning ion microscope analysis may include irradiating a cross section of the positive electrode active material with a focused ion beam to obtain a scanning ion microscope image, obtaining segmented data in units of crystal grains from the scanning ion microscope image using deep learning, and calculating the DoA represented by Equation 1 from the segmented data.

[0014] Meanwhile, the Electron Backscatter Diffraction (EBSD) analysis may be performed by obtaining EBSD Euler map data including position information and Euler angle information of each crystal grain through EBSD measurement of a cross section of the positive electrode active material, and calculating a c-axis rotation vector Rc(x, y, z) of a crystal lattice of the crystal grain according to the following [Equation 2]: [Formula 2]

number

[0015] Preferably, the positive electrode active material may further include crystal grains A having a DoA of 0.5 to 1 and a crystal grain c-axis orientation degree of 0.5 to 1, crystal grains B having a DoA of less than 0.5 and a crystal grain c-axis orientation degree of 0.5 to 1, and crystal grains D having a DoA of less than 0.5 and a crystal grain c-axis orientation degree of less than 0.5, and of all crystal grains in a cross section of the positive electrode active material particle, a proportion of crystal grains A may be 20% or more and less than 25%, a proportion of crystal grains B may be 5% to 30%, a proportion of crystal grains C may be 25% to 70%, and a proportion of crystal grains D may be 5% to 30%.

[0016] In this case, the total proportion of crystal grains A and crystal grains C among all crystal grains in the cross section of the positive electrode active material particle may be 50% to 90%, and preferably 50% to 80%.

[0017] On the other hand, the positive electrode active material may have a crystal grain size of 70 nm to 200 nm, preferably 100 nm to 180 nm, and more preferably 100 nm to 150 nm.

[0018] The positive electrode active material may have a microstrain of 0.04% to 0.25%, preferably 0.06% to 0.15%.

[0019] The positive electrode active material may have primary particles with an average particle size of 0.05 μm to 8 μm, preferably 0.1 μm to 4 μm, and secondary particles with an average particle size of 2 μm to 25 μm, preferably 4 μm to 18 μm.

[0020] Meanwhile, the positive electrode active material may be a lithium transition metal composite oxide represented by the following [Chemical Formula 1].

[0021] [Chemical formula 1] Li x [Ni a Co b M 1 c M 2 d ]O 2-y A y In the above [Chemical Formula 1], Said M 1 is one or more elements selected from the group consisting of Mn and Al, 2 is one or more elements selected from the group consisting of W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, Ta, Y, In, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B, and Mo, and A is one or more elements selected from the group consisting of F, Cl, Br, I, At, and S, and 0.98≦x≦1.20, 0 <a<1、0<b<1、0<c<1、0≦d≦0.2、0≦y≦0.2である。

[0022] According to another embodiment, the present invention provides a positive electrode including the positive electrode active material according to the present invention, and a lithium secondary battery including the positive electrode. Effect of the Invention

[0023] The positive electrode active material of the present invention contains a specific ratio of crystal grains having high long axis orientation and low c-axis orientation, and can realize excellent capacity characteristics and gas generation reduction characteristics when applied to a secondary battery. [Brief description of the drawings]

[0024] [Figure 1] FIG. 2 is a scanning ion microscope image of a cross section of a positive electrode active material. [Diagram 2] 1A to 1C are diagrams illustrating a process of obtaining a segmentation image by analyzing a scanning ion microscope image of a cross section of a positive electrode active material. [Diagram 3] FIG. 1 is a diagram showing the long axis orientation of crystal grains and the DoA value. [Figure 4] FIG. 2 is a diagram showing an EBSD Euler map obtained by EBSD analysis of a cross section of a positive electrode active material. [Diagram 5] FIG. 2 shows a c-axis orientation map of crystal grains. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0025] The terms and words used in this specification and the claims should not be interpreted limited to their ordinary and dictionary meanings, but should be interpreted in a way that is consistent with the technical ideas of the present invention, based on the principle that the inventor himself / herself can appropriately define the concepts of terms in order to explain the invention in the best possible way.

[0026] In the present invention, "crystallite" means a single crystal particle unit having a regular atomic arrangement. The size of the crystallite can be measured by analyzing the X-ray diffraction data of the cross-section of the positive electrode active material by the Rietveld refinement method. For example, the size of the crystallite can be obtained by performing X-ray diffraction analysis under the following conditions using Empyreon XRD equipment of Malyer Panalyticla to obtain XRD data, and then processing the XRD data using the Highscore program of Malyer Panalytical. At this time, the half-width was set to be measured using the Caglioti equation.

[0027] <Conditions for X-ray diffraction analysis> Light source: Cu-target, 45 kV, 40 mA output, wavelength = 1.54 Å Detector: GaliPIX3D Sample preparation: A sample of about 5 g was filled into a holder with a diameter of 2 cm and loaded onto a rotation stage.

[0028] Measurement time: About 30 minutes Measurement range: 2θ = 15° to 85°

[0029] In the present invention, "primary particle" means the smallest particle unit that can be distinguished as a whole when observing the cross-section of the positive electrode active material through a scanning ion microscope (SEM), and it may consist of one crystallite or a plurality of crystallites. In the present invention, the average particle size of the primary particles can be measured by measuring the respective particle sizes distinguished from the cross-section SEM data of the positive electrode active material particles and then obtaining the arithmetic mean value thereof.

[0030] In the present invention, "secondary particle" means a secondary structure formed by the aggregation of a plurality of primary particles. The average particle size of the secondary particles may be measured using a particle size analyzer. In the present invention, s3500 of Microtrac was used as the particle size analyzer.

[0031] In the present invention, "microstrain" is a value measured by Rietveld analysis of X-ray diffraction data, and indicates the degree of deformation of the crystal lattice.

[0032] On the other hand, in the present invention, the proportion (%) of each crystal grain means (the number of the crystal grain / the total number of crystal grains present in the cross section of the positive electrode active material particle)×100.

[0033] The present invention will be specifically described below.

[0034] The present inventors conducted extensive research to develop a positive electrode active material that, when applied to a secondary battery, can not only improve the capacity characteristics of the secondary battery but also reduce the amount of gas generated during charging and discharging of the secondary battery. As a result, they discovered that when the proportion of crystal grains in the positive electrode active material that have a high long axis orientation and a low c-axis orientation satisfies a specific range, the capacity characteristics and gas generation reduction characteristics of the secondary battery can be improved, and completed the present invention.

[0035] positive electrode active material The positive electrode active material according to the present invention is characterized in that the degree of crystal grain long axis orientation DoA represented by [Formula 1] is 0.5 to 1, and the proportion of crystal grains C having a degree of crystal grain c-axis orientation of less than 0.5 accounts for 25% to 70% of all crystal grains in the cross section of the positive electrode active material particle.

[0036] [Formula 1]

number

[0037] In the formula 1, λ1 is the long axis vector E of the crystal grain measured from image data obtained by scanning ion microscope analysis of the cross section of the positive electrode active material. I λ2 is the magnitude of the short axis vector E of the crystal grain measured from image data obtained by analyzing the cross section of the positive electrode active material with a scanning ion microscope. II is the size of C D is the position unit vector P' and the major axis unit vector E of the grainI ' is the dot product value.

[0038] First, the DoA expressed by the above [Equation 1] will be explained.

[0039] The DoA value represented by the above formula (1) indicates the orientation of the long axis of crystal grains, and can be determined using data obtained by scanning ion microscope analysis.

[0040] Specifically, a cross section of the positive electrode active material is irradiated with a focused ion beam to obtain a scanning ion microscope image, and then deep learning is used to obtain segmented data in units of crystal grains from the scanning ion microscope image, and the degree of crystal grain long axis orientation DoA, expressed by the above [Equation 1], can be calculated from the segmented data.

[0041] The method of determining the DoA value by scanning ion microscope analysis will be described in more detail below.

[0042] A scanning ion microscope is a device that measures the surface structure of a sample through a signal ion image generated when an ion beam is scanned over the surface of the sample. In this case, since the reflectance of the ion beam changes at different crystal planes, a scanning ion microscope can be used to obtain a cross-sectional image of a positive electrode active material particle separated into single crystal grain units having the same atomic arrangement structure. FIG. 1 shows a scanning ion microscope image of a cross-section of a positive electrode active material particle. It can be seen from FIG. 1 that the cross-sectional image of the positive electrode active material particle is separated into crystal grain units.

[0043] Next, the scanning ion microscope image thus obtained is analyzed to obtain data segmented into grain units, and the image analysis may be performed using deep learning.

[0044] A process of analyzing a scanning ion microscope image to obtain segmented data information is shown in Fig. 2. As shown in Fig. 2, the image analysis may be performed, for example, by detecting a boundary line from a scanning ion microscope image by deep learning, and then obtaining image data segmented in units of crystal grains using the boundary line.

[0045] In this case, the detection of the boundary may be performed using an AutoEncoder Neural Network (U-NET) algorithm, and the segmentation may be performed using a Watershed segmentation algorithm or the like.

[0046] Since a scanning ion microscope image itself does not contain quantified information, in the present invention, data information segmented into each crystal grain unit is obtained by deep learning, thereby making it possible to quantify information such as the shape and position of the crystal grains.

[0047] When segmented data is obtained by the above-mentioned scanning ion microscope image analysis, the position vector, major axis vector, and minor axis vector of the crystal grain to be measured can be obtained from the data, and the DoA value of Equation 1 can be calculated using the above.

[0048] [Formula 1]

number

[0049] In the formula 1, λ1 is the long axis vector E of the crystal grain measured from image data obtained by scanning ion microscope analysis of the cross section of the positive electrode active material. I At this time, the magnitude of the major axis vector E I means, among the vectors passing through the center of gravity of the crystal grain, the vector having the smallest sum of the distance between the vector and each pixel in the crystal grain.

[0050] λ2 is the short axis vector E of the crystal grain measured from image data obtained by analyzing the cross section of the positive electrode active material with a scanning ion microscope. II At this time, the magnitude of the short axis vector E II means the vector that passes through the center of gravity of the crystal grain and has the largest sum of the distance between the vector and each pixel in the crystal grain.

[0051] On the other hand, C D is the position unit vector P' of the grain and the major axis unit vector E I The position unit vector P′ of the crystal grain is a vector obtained by converting a position vector connecting the center of the cross section of the positive electrode active material particle to the center of gravity of the crystal grain so that the magnitude of the vector is 1, and the major axis unit vector E I ' is the major axis vector E I is a vector converted so that the magnitude becomes 1. In this case, the center of the cross section of the positive electrode active material particle is the center of mass in a two-dimensional image (scanning ion microscope image of the cross section of the positive electrode active material).

[0052] The DoA value calculated by the formula 1 indicates the degree to which the long axis of the crystal grain is inclined with respect to the line passing through the center of the positive electrode active material and the center of gravity of the crystal grain, and the closer the DoA value is to 1, the smaller the angle between the long axis of the crystal grain and the line, and the closer the DoA value is to 0, the larger the angle between the long axis of the crystal grain and the line. In other words, the closer the DoA is to 1, the higher the long axis orientation of the crystal grain.

[0053] A diagram showing the DoA values ​​obtained by the above method and the long axis of the crystal grain is shown in Figure 3. As shown in Figure 3, in the case of crystal grain 1, in which the angle between the long axis of the crystal grain and the line passing through the center of the positive electrode active material and the center of gravity of the crystal grain is small, the DoA is 0.965, which is close to 1, whereas in the case of crystal grain 2, in which the angle between the long axis of the crystal grain and the line passing through the center of the positive electrode active material and the center of gravity of the crystal grain is large, the DoA is 0.352, which is small.

[0054] Meanwhile, by mapping the information on the degree of orientation of each crystal grain's major axis, the proportion of crystal grains having a specific value of the degree of orientation of the major axis in the cross section of the positive electrode active material particle can be measured.

[0055] Next, the degree of crystal grain c-axis orientation will be described.

[0056] The crystal grain c-axis orientation indicates the orientation of the c-axis of the crystal lattice of the crystal grain, and is the cross product of the c-axis rotation vector Rc of the crystal lattice of the crystal grain obtained by electron backscatter diffraction (EBSD) analysis and the position unit vector P' of the crystal grain.

[0057] Specifically, the degree of crystal grain c-axis orientation can be obtained by obtaining EBSD Euler map data including position information and Euler angle information of each crystal grain by electron backscatter diffraction (EBSD) measurement of a cross section of the positive electrode active material, determining the c-axis rotation vector Rc of the crystal lattice using the EBSD Euler map data, and calculating the cross product of the c-axis rotation vector Rc of the crystal lattice and the position unit vector P' of the crystal grain.

[0058] The method for determining the crystal grain c-axis orientation degree according to the present invention will now be described in detail.

[0059] Electron backscatter diffraction analysis is a method of measuring the crystallographic phase and crystallographic orientation of a sample using the diffraction pattern of the sample, and analyzing the crystallographic information of the sample based on the results. In a scanning electron microscope, when a sample (i.e., a cross-section of a positive active material) is tilted at a large angle to the direction of incidence of the electron beam, the incident electron beam is scattered within the sample, and a diffraction pattern appears in the direction of the sample surface, which is called an electron backscatter diffraction pattern (EBSP). Since the electron backscatter diffraction pattern responds to the crystal orientation of the area irradiated with the electron beam, it can be used to accurately measure the crystal orientation of the sample, and Euler map data containing various information on the crystal orientation of the entire sample can be obtained using EBSD software. Figure 4 shows an Euler map obtained by analyzing the cross-section of a positive active material particle using electron backscatter diffraction (EBSD).

[0060] The EBSD Euler map data includes position vector information and Euler angle information of each crystal grain. On the other hand, by using the Euler angle information, the c-axis rotation vector Rc of the crystal lattice in each crystal grain can be obtained.

[0061] The c-axis rotation vector Rc of the crystal lattice indicates the direction in which the c-axis of the crystal grain is rotated with respect to a line passing through the center of gravity of the crystal grain and the center of the positive electrode active material.

[0062] Specifically, the c-axis rotation vector Rc of the crystal lattice may be (x, y, z) calculated by the following [Equation 2].

[0063] [Formula 2]

number

[0064] In the above [Equation 2], [X, Y, Z] are (0, 0, 1), and ψ, θ, and φ are the Euler angles of each crystal grain obtained from the Euler map data.

[0065] The degree of crystal grain orientation can be calculated using the c-axis rotation vector Rc of the crystal lattice calculated as described above and the position vector information of each crystal grain included in the Euler map data. Specifically, the degree of crystal grain orientation can be quantified as the cross product of the c-axis rotation vector Rc of the crystal lattice and the position unit vector P' of the crystal grain.

[0066] In this case, the position unit vector P' means that the position vector of the crystal grain is converted so that the magnitude is 1. For example, if the position vector of the crystal grain is (a, b, 0), the position unit vector is

number

[0067] The cross product of the position unit vector P' and the c-axis rotation vector Rc of the crystal lattice is a numerical value indicating the degree of orientation of the crystal grain c-axis in the positive electrode active material particle. Specifically, when the cross product of the position unit vector P' and the c-axis rotation vector Rc of the crystal lattice is 1, it means that the c-axis of the crystal grain is arranged perpendicular to the line passing through the center of the positive electrode active material particle and the center of gravity of the crystal grain, and when the cross product is 0, it means that the c-axis of the crystal grain is arranged horizontally to the line.

[0068] In the positive electrode active material, the mobility of lithium ions when moving along a direction perpendicular to the c-axis is 10 times faster than when moving along the c-axis. Therefore, a lithium path is formed along a direction perpendicular to the c-axis. In addition, when the lithium path is formed parallel to a line passing through the center of the positive electrode active material particle and the center of gravity of the crystal grain, the lithium migration distance is minimized, and the lithium conductivity is improved. Therefore, it can be determined that the closer the cross product value of the position unit vector P' and the c-axis rotation vector Rc of the crystal lattice is to 1, the better the c-axis orientation of the crystal grain.

[0069] Meanwhile, by integrating the c-axis orientation degree of each crystal grain obtained as described above, the c-axis orientation degree of all crystal grains in the cross section of the positive electrode active material particle can be obtained. FIG. 5 shows a crystal grain c-axis orientation map of the positive electrode active material obtained by integrating the c-axis orientation degree of each crystal grain. In FIG. 5, the closer to red, the better the c-axis orientation, and the closer to blue, the lower the c-axis orientation. By using the c-axis orientation map as described above, the proportion of crystal grains that satisfy the c-axis orientation condition in the cross section of the positive electrode active material particle can be obtained.

[0070] According to the research of the present inventor, the ratio of crystal grains (hereinafter referred to as crystal grains C) having a crystal grain long axis orientation degree DoA of 0.5 to 1 and a crystal grain c-axis orientation degree of less than 0.5 in the cross section of the positive electrode active material particle may be 25% to 70%, preferably 25% to 60%, more preferably 30% to 65%, and even more preferably 30% to 45%. When the ratio of crystal grains C satisfies the above range, it has been shown that excellent capacity characteristics and gas generation reduction characteristics can be realized. When the ratio of crystal grains C is less than 25%, the improvement effect of capacity characteristics and gas generation characteristics cannot be obtained, and when it exceeds 70%, not only the life characteristics are deteriorated but also the improvement effect of gas generation characteristics cannot be obtained.

[0071] On the other hand, the positive electrode active material according to the present invention may further include, in addition to the crystal grains C, crystal grains having a crystal grain c-axis orientation degree of 0.5 to 1 and a crystal grain long axis orientation degree DoA of 0.5 to 1 (hereinafter referred to as crystal grains A), crystal grains having a crystal grain c-axis orientation degree of 0.5 to 1 and a crystal grain long axis orientation degree DoA of less than 0.5 (hereinafter referred to as crystal grains B), and crystal grains having a crystal grain c-axis orientation degree of less than 0.5 and a crystal grain long axis orientation degree DoA of less than 0.5 (hereinafter referred to as crystal grains D). Of all the crystal grains in the cross section of the positive electrode active material particle, the proportion of crystal grains A may be 20% or more and less than 25%, the proportion of crystal grains B may be 5% to 30%, the proportion of crystal grains C may be 25% to 70%, and the proportion of crystal grains D may be 5% to 30%.

[0072] In this case, the total ratio of crystal grains A and crystal grains C to all crystal grains in the cross section of the positive electrode active material particle is preferably 50% to 90%, specifically 50% to 80%, and more specifically 55% to 65%. When the ratio of crystal grains A and crystal grains C satisfies the above range, more excellent effects can be obtained in terms of capacity characteristics and life characteristics, especially life characteristics.

[0073] Meanwhile, the ratio of crystal grains in a positive electrode active material varies depending on the composition of a precursor used in producing the positive electrode active material, the shape and orientation of the crystal grains of the precursor, the type of doping element, and / or the firing temperature, etc., and therefore, by appropriately adjusting the type of precursor, the doping element, the firing temperature, etc., a positive electrode active material satisfying the ratio of crystal grains of the present invention can be produced.

[0074] Meanwhile, the positive electrode active material according to the present invention may be a lithium composite transition metal oxide containing two or more transition metals, for example, a lithium composite transition metal oxide represented by the following [Chemical Formula 1].

[0075] [Chemical formula 1] Li x [Ni a Co b M 1 c M 2 d ]O 2-y A y In the above [Chemical Formula 1], the M 1 may be one or more elements selected from the group consisting of Mn and Al.

[0076] The M 2 may be one or more elements selected from the group consisting of W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, Ta, Y, In, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B, and Mo.

[0077] Also, the A may be one or more elements selected from the group consisting of F, Cl, Br, I, At, and S.

[0078] The x represents the ratio of the number of moles of Li to the total number of moles of transition metals, and 0.98 ≤ x ≤ 1.20, preferably 0.99 ≤ x ≤ 1.10, more preferably 1.0 ≤ x ≤ 1.10.

[0079] The a represents the ratio of the number of moles of Ni to the total number of moles of transition metals, and 0 < a < 1, preferably 0.3 ≤ a < 1, more preferably 0.6 ≤ a < 1, still more preferably 0.8 ≤ a < 1.

[0080] The b represents the ratio of the number of moles of Co to the total number of moles of transition metals, and 0 < b < 1, preferably 0 < b < 0.7, more preferably 0 < b < 0.4, still more preferably 0 < b < 0.2.

[0081] The c represents the ratio of the number of moles of M 1 to the total number of moles of transition metals, and 0 < c < 1, preferably 0 < c < 0.7, more preferably 0 < c < 0.4, still more preferably 0 < c < 0.2.

[0082] The d represents the ratio of the number of moles of M 2 to the total number of moles of transition metals, and 0 ≤ d ≤ 0.2, preferably 0 ≤ d ≤ 0.15, more preferably 0 ≤ d ≤ 0.10.

[0083] The y indicates the ratio of the number of moles of the A element substituted at the oxygen site, and may be 0≦y≦0.2, preferably 0≦y≦0.15, and more preferably 0≦y≦0.10.

[0084] Meanwhile, the positive electrode active material may have a crystal grain size of 70 nm to 200 nm, preferably 100 nm to 180 nm, more preferably 100 nm to 150 nm. If the crystal grain size is too large, a rock salt phase is formed, which may reduce the resistance characteristics and life characteristics, and if the crystal grain size is too small, the contact area with the electrolyte increases, which may cause rapid deterioration.

[0085] The positive electrode active material may have a microstrain of 0.04% to 0.25%, preferably 0.06 to 0.15%. If the microstrain is too large, the life characteristics deteriorate, and if it is too small, the lithium ion mobility deteriorates.

[0086] The positive electrode active material may have an average primary particle size of 0.05 μm to 8 μm, preferably 0.1 μm to 2 μm. If the average primary particle size is too large, a rocksalt phase is formed, which may reduce the resistance characteristics and life characteristics, whereas if the average primary particle size is too small, the contact area with the electrolyte increases, which may cause rapid deterioration.

[0087] The positive electrode active material may have an average secondary particle size of 2 μm to 25 μm, preferably 4 μm to 18 μm. When the average secondary particle size falls within this range, it is possible to prevent the positive electrode active material particles from being broken during the rolling process or to prevent the processability from being reduced during the production of the slurry.

[0088] positive electrode Next, the positive electrode according to the present invention will be described.

[0089] The positive electrode includes a positive electrode active material according to the present invention. Specifically, the positive electrode includes a positive electrode current collector and a positive electrode active material layer formed on the positive electrode current collector, and the positive electrode active material layer includes the positive electrode active material according to the present invention.

[0090] Here, the positive electrode active material is the same as that described above, so a detailed description thereof will be omitted, and only the remaining components will be described in detail below.

[0091] The positive electrode current collector may contain a metal with high conductivity, and the positive electrode active material layer may be easily attached, but is not particularly limited as long as it is non-reactive within the voltage range of the battery. The positive electrode current collector may be, for example, stainless steel, aluminum, nickel, titanium, baked carbon, or aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, etc. The positive electrode current collector may have a thickness of typically 3 to 500 μm, and fine irregularities may be formed on the surface of the current collector to increase the adhesive strength of the positive electrode active material. For example, the positive electrode current collector may be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.

[0092] The positive electrode active material layer may selectively contain a conductive material, a binder, and a dispersant, as necessary, in addition to the positive electrode active material.

[0093] In this case, the positive electrode active material may be contained in an amount of 80 to 99 wt %, more specifically, 85 to 98.5 wt %, based on the total weight of the positive electrode active material layer. When contained in this range, excellent capacity characteristics can be exhibited.

[0094] The conductive material is used to impart conductivity to the electrode, and can be used without any particular restrictions as long as it has electronic conductivity without causing chemical changes in the battery that is constructed. Specific examples include graphite such as natural graphite and artificial graphite; carbon-based materials such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fibers; metal powders or metal fibers such as copper, nickel, aluminum, and silver; conductive tubes such as carbon nanotubes; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive polymers such as polyphenylene derivatives, and one or more of these may be used alone or in combination. The conductive material may be contained in an amount of 0.1 to 15% by weight based on the total weight of the positive electrode active material layer.

[0095] The binder serves to improve the adhesion between the positive electrode active material particles and the adhesive strength between the positive electrode active material and the current collector.Specific examples of the binder include polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylalcohol, polyacrylonitrile, polymethyl methacrylate, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber, polyacrylic acid, and polymers in which hydrogen is substituted with Li, Na, or Ca, or various copolymers thereof, and one or more of these may be used alone or in combination. The binder may be contained in an amount of 0.1 to 15% by weight based on the total weight of the positive electrode active material layer.

[0096] The dispersant may include a water-based dispersant or an organic dispersant such as N-methyl-2-pyrrolidone.

[0097] The positive electrode may be manufactured by a method for manufacturing a positive electrode, except for using the positive electrode active material. Specifically, the positive electrode may be manufactured by dissolving or dispersing the positive electrode active material and, optionally, a binder, a conductive material, and a dispersant in a solvent to prepare a positive electrode slurry composition, which is applied onto a positive electrode current collector, followed by drying and rolling.

[0098] The solvent may be a solvent commonly used in the art, such as dimethyl sulfoxide (DMSO), isopropyl alcohol, N-methylpyrrolidone (NMP), dimethyl formamide (DMF), acetone, or water, and one or more of these may be used alone or in combination. The amount of the solvent used is sufficient to dissolve or disperse the positive electrode active material, conductive material, binder, and dispersant in consideration of the coating thickness of the slurry and the manufacturing yield, and to have a viscosity that can show excellent thickness uniformity when applied to manufacture a positive electrode.

[0099] Alternatively, the positive electrode may be manufactured by casting the positive electrode slurry composition on a separate support, peeling the composition from the support, and laminating the resulting film on a positive electrode current collector.

[0100] secondary battery In addition, the present invention can provide an electrochemical device including the positive electrode. The electrochemical device may be, for example, a battery or a capacitor, and more specifically, a lithium secondary battery.

[0101] Specifically, the lithium secondary battery may include a positive electrode, a negative electrode facing the positive electrode, and a separator and an electrolyte interposed between the positive electrode and the negative electrode. Since the positive electrode is as described above, detailed description thereof will be omitted, and only the remaining components will be described in detail below.

[0102] The lithium secondary battery may optionally further include a battery container that houses an electrode assembly including the positive electrode, the negative electrode, and the separator, and a sealing member that seals the battery container.

[0103] In the lithium secondary battery, the negative electrode includes a negative electrode current collector and a negative electrode active material layer located on the negative electrode current collector.

[0104] The negative electrode current collector is not particularly limited as long as it does not cause a chemical change in the battery and has high conductivity, and may be, for example, copper, stainless steel, aluminum, nickel, titanium, calcined carbon, copper or stainless steel surface treated with carbon, nickel, titanium, silver, or aluminum-cadmium alloy. The negative electrode current collector may have a thickness of typically 3 μm to 500 μm, and like the positive electrode current collector, the surface of the current collector may be formed with fine irregularities to strengthen the binding force of the negative electrode active material. For example, the negative electrode current collector may be used in various forms such as a film, sheet, foil, net, porous body, foam, or nonwoven fabric.

[0105] The negative electrode active material layer includes a negative electrode active material, and optionally a binder and a conductive material.

[0106] The negative electrode active material may be a compound capable of reversible intercalation and deintercalation of lithium. Specific examples of the negative electrode active material include carbonaceous materials such as artificial graphite, natural graphite, graphitized carbon fiber, and amorphous carbon; metallic compounds capable of alloying with lithium, such as Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd, Si alloys, Sn alloys, and Al alloys; SiO β(0<β<2), metal oxides capable of doping and dedoping lithium, such as SnO2, vanadium oxide, and lithium vanadium oxide; or composites containing the metallic compounds and carbonaceous materials, such as Si-C composites and Sn-C composites, and any one or a mixture of two or more of these may be used. In addition, a metallic lithium thin film may be used as the negative electrode active material. In addition, both low-crystalline carbon and high-crystalline carbon may be used as the carbon material. Representative examples of low crystalline carbon include soft carbon and hard carbon, and representative examples of high crystalline carbon include amorphous, plate-like, scaly, spherical or fibrous natural graphite, artificial graphite, kish graphite, pyrolytic carbon, mesophase pitch based carbon fiber, meso-carbon microbeads, mesophase pitches, and high-temperature fired carbon such as petroleum or coal tar pitch derived cokes.

[0107] The negative electrode active material may be included in an amount of 80% by weight to 99% by weight based on the total weight of the negative electrode active material layer.

[0108] The binder is a component that aids in bonding between the conductive material, the active material, and the current collector, and may be included in an amount of 0.1% by weight to 10% by weight based on the total weight of the negative electrode active material layer. Examples of such binders include polyvinylidene fluoride (PVDF), polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated EPDM, styrene-butadiene rubber (SBR), nitrile-butadiene rubber, fluororubber, and various copolymers thereof.

[0109] The conductive material is a component for further improving the conductivity of the negative electrode active material, and may be added in an amount of 10% by weight or less, preferably 5% by weight or less, based on the total weight of the negative electrode active material layer. Such a conductive material is not particularly limited as long as it does not cause a chemical change in the battery and has conductivity, and examples of such conductive materials include graphite such as natural graphite and artificial graphite; carbon black such as acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black; conductive fibers such as carbon fibers and metal fibers; metal powders such as carbon fluoride, aluminum, and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive materials such as polyphenylene derivatives.

[0110] For example, the negative electrode active material layer may be prepared by coating a negative electrode slurry composition prepared by dissolving or dispersing a negative electrode active material and, optionally, a binder and a conductive material in a solvent on a negative electrode current collector and drying the coating, or by casting the negative electrode slurry composition on a separate support and peeling the composition from the support to obtain a film, which may be laminated on the negative electrode current collector.

[0111] Meanwhile, in the lithium secondary battery, the separator separates the negative electrode and the positive electrode and provides a passage for lithium ions to move. Any separator generally used in lithium secondary batteries may be used without any particular limitations. In particular, a separator having low resistance to ion movement of the electrolyte and excellent electrolyte impregnation ability is preferred. Specifically, a porous polymer film, for example, a porous polymer film made of a polyolefin-based polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, and an ethylene / methacrylate copolymer, or a laminate structure of two or more layers thereof may be used. In addition, a conventional porous nonwoven fabric, for example, a nonwoven fabric made of high-melting glass fiber, polyethylene terephthalate fiber, etc. may be used. In addition, a coated separator containing a ceramic component or a polymeric material may be used to ensure heat resistance or mechanical strength, and may be selectively used in a single layer or multilayer structure.

[0112] In addition, examples of the electrolyte used in the present invention include organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel polymer electrolytes, solid inorganic electrolytes, and molten inorganic electrolytes that can be used in the production of lithium secondary batteries, but are not limited to these.

[0113] Specifically, the electrolyte may include an organic solvent and a lithium salt.

[0114] The organic solvent may be any solvent that can move ions involved in the electrochemical reaction of the battery without any particular limitation. Specifically, the organic solvent may be an ester solvent such as methyl acetate, ethyl acetate, γ-butyrolactone, or ε-caprolactone; an ether solvent such as dibutyl ether or tetrahydrofuran; a ketone solvent such as cyclohexanone; an aromatic hydrocarbon solvent such as benzene or fluorobenzene; dimethylcarbonate (DMC), diethylcarbonate (DEC), ethylmethylcarbonate (EMC), ethylene carbonate (EC), or propylene carbonate (propylene carbonate). Examples of suitable solvents include carbonate-based solvents such as ethylene carbonate (PC), alcohol-based solvents such as ethyl alcohol and isopropyl alcohol, nitriles such as R-CN (R is a straight-chain, branched or cyclic hydrocarbon group having 2 to 20 carbon atoms, which may contain a double bond aromatic ring or an ether bond), amides such as dimethylformamide, dioxolanes such as 1,3-dioxolane, and sulfolanes. Among these, carbonate-based solvents are preferred, and a mixture of a cyclic carbonate (e.g., ethylene carbonate or propylene carbonate) having high ionic conductivity and high dielectric constant, which can enhance the charge / discharge performance of a battery, and a low-viscosity linear carbonate compound (e.g., ethyl methyl carbonate, dimethyl carbonate or diethyl carbonate) is more preferred. In this case, the cyclic carbonate and the chain carbonate are mixed in a volume ratio of about 1:1 to about 1:9, and the electrolyte solution may exhibit excellent performance.

[0115] The lithium salt can be used without any particular limitation as long as it is a compound that can provide lithium ions used in a lithium secondary battery. Specifically, the anion of the lithium salt is F - , Cl - , Br - , I - , NO3 - , N(CN)2 - , BF4 - , CF3CF2SO3 - , (CF3SO2)2N - , (FSO2)2N - , CF3CF2(CF3)2CO - , (CF3SO2)2CH - , (SF5)3C - , (CF3SO2)3C - , CF3(CF2)7SO3 - , CF3CO2 - , CH3CO2 - , SCN - and (CF3CF2SO2)2N - The lithium salt may be at least one selected from the group consisting of LiPF6, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4, LiCF3SO3, LiC4F9SO3, LiN(C2F5SO3)2, LiN(C2F5SO2)2, LiN(CF3SO2)2, LiCl, LiI, or LiB(C2O4)2. The lithium salt is preferably used in a concentration range of 0.1M to 2.0M. When the lithium salt concentration is within the above range, the electrolyte has appropriate conductivity and viscosity, so that excellent electrolyte performance can be exhibited and lithium ions can be effectively transferred.

[0116] As described above, the lithium secondary battery including the positive electrode active material according to the present invention exhibits excellent capacity characteristics and reduced gas generation characteristics, and can be usefully used in various fields such as portable devices such as mobile phones, notebook computers, and digital cameras, and electric vehicles.

[0117] Hereinafter, the present invention will be described in detail with reference to examples in order to specifically explain the present invention. However, the examples according to the present invention may be modified in various different forms, and the scope of the present invention should not be construed as being limited by the following examples. The examples of the present invention are provided to more completely explain the present invention to those having average knowledge in the art.

[0118] Working Example Production Example 1 - Production of Positive Electrode Active Material Precursor A NiSO4, CoSO4, and MnSO4 were mixed in distilled water in amounts such that the molar ratio of nickel:cobalt:manganese was 92:4:4 to prepare a 2.4 M transition metal aqueous solution.

[0119] Next, deionized water was added to the reactor, and nitrogen gas was purged into the reactor to remove dissolved oxygen in the water and create a non-oxidizing atmosphere in the reactor. Then, 7.96 M NaOH was added to maintain the pH in the reactor at 11.9.

[0120] Thereafter, the aqueous transition metal solution was added to the reactor at a rate of 850 mL / hr, the aqueous NaOH solution was added at a rate of 510 mL / hr, and the aqueous NH4OH solution was added at a rate of 160 mL / hr. The reaction was allowed to proceed for 40 hours under the conditions of a reaction temperature of 50° C., pH 11.4, and a stirring speed of 600 rpm. The average particle size (D 50 ) is 13μm, and Ni 0.92 Co 0.04 Mn 0.04 A positive electrode active material precursor A represented by (OH)2 was prepared.

[0121] Production Example 2 - Production of Positive Electrode Active Material Precursor B The average particle size (D 50 ) is 4μm, and Ni 0.92 Co 0.04 Mn 0.04 A positive electrode active material precursor B represented by (OH)2 was prepared.

[0122] Example 1 The positive electrode active material precursor A prepared in Preparation Example 1 was mixed with LiOH so that the molar ratio of Li:transition metal was 1.05:1, and Nb2O3 was added thereto so that the molar ratio of Nb:transition metal was 0.00125:1. The mixture was then calcined at 760° C. for 13 hours to obtain Li[Ni 0.92 Co 0.04 Mn 0.04 ] 0.99875 Nb 0.00125 Manufactured the O2.

[0123] Then, the Li[Ni 0.92 Co 0.04 Mn 0.04 ] 0.99875 Nb 0.00125 O2 was washed with water and dried, and then mixed with 500 ppm of boric acid and heat-treated at 300° C. to produce B-coated positive electrode active material 1.

[0124] Example 2 Positive electrode active material 2 was produced in the same manner as in Example 1, except that Nb2O3 was added and mixed so that the molar ratio of Nb:transition metal was 0.0025:1.

[0125] Comparative Example 1 The positive electrode active material precursor A prepared in Preparation Example 1 and LiOH were mixed so that the molar ratio of Li:transition metal was 1.05:1, and the mixture was fired at 760° C. for 13 hours to obtain Li[Ni 0.92 Co 0.04 Mn 0.04 ]O2 was produced.

[0126] Then, the Li[Ni 0.92 Co 0.04 Mn 0.04 ]O2 was washed with water and dried, and then mixed with 500 ppm of boric acid and heat-treated at 300° C. to produce B-coated positive electrode active material 3.

[0127] Comparative Example 2 The positive electrode active material precursor A prepared in Preparation Example 1 was mixed with LiOH so that the molar ratio of Li:transition metal was 1.05:1, and Ta2O3 was added thereto so that the molar ratio of Ta:transition metal was 0.0025:1. The mixture was then calcined at 760° C. for 13 hours to obtain Li[Ni 0.92 Co 0.04 Mn 0.04 ] 0.9975 Ta 0.0025 Manufactured the O2.

[0128] Then, the Li[Ni 0.92 Co 0.04 Mn 0.04 ] 0.9975 Ta 0.0025 O2 was washed with water and dried, and then mixed with 500 ppm of boric acid and heat-treated at 300° C. to produce B-coated positive electrode active material 4.

[0129] Comparative Example 3 The positive electrode active material precursor B prepared in Preparation Example 2 was mixed with LiOH so that the molar ratio of Li:transition metal was 1.05:1, and Nb2O3 was added thereto so that the molar ratio of Nb:transition metal was 0.0025:1. The mixture was then fired at 770° C. for 13 hours to obtain Li[Ni 0.92 Co 0.04 Mn 0.04 ] 0.9975 Nb 0.0025 Manufactured the O2.

[0130] Then, the Li[Ni 0.92 Co 0.04 Mn 0.04 ] 0.9975 Nb 0.0025 O2 was washed with water and dried, and then mixed with 500 ppm of boric acid and heat-treated at 300° C. to produce B-coated positive electrode active material 5.

[0131] Experimental Example 1: Analysis of Positive Electrode Active Material Using an ion milling system (Hitachi, IM4000), each of the positive electrode active materials 1 to 5 produced in Examples 1 to 2 and Comparative Examples 1 to 3 was cross-sectionally cut, and then the above-mentioned scanning ion microscope analysis and electron backscatter diffraction (EBSD) analysis were performed to measure the proportions of crystal grains A, B, C, and D.

[0132] In addition, the XRD data of the positive electrode active materials 1 to 5 prepared in Examples 1 to 2 and Comparative Examples 1 to 3 were measured using Malvern Panalytical's Empyrean equipment, and the crystal size and micro strain of each positive electrode active material were measured using the Rietveld method built into Malvern Panalytical's Highscore program.

[0133] The measurement results are shown in Table 1 below.

[0134] [Table 1]

[0135] Experimental Example 2: Evaluation of battery characteristics The positive electrode active materials prepared in Examples 1-2 and Comparative Examples 1-3, a conductive material (denka black), and a binder (PVDF) were mixed in a weight ratio of 97.5:1:1.5 in N-methyl-2-pyrrolidone (NMP) solvent to prepare a positive electrode slurry. The positive electrode slurry was applied to one side of an aluminum current collector, dried, and then rolled to prepare a positive electrode.

[0136] A lithium metal electrode was used as the negative electrode.

[0137] The electrode assembly was prepared by interposing a separator between the positive electrode and the negative electrode, and then placed inside a battery case, and an electrolyte was injected to prepare a lithium secondary battery. The electrolyte was prepared by dissolving 1M LiPF6 in an organic solvent in which ethylene carbonate: ethyl methyl carbonate: diethyl carbonate was mixed in a volume ratio of 3:3:4.

[0138] Then, the secondary batteries were charged at a constant current of 0.1 C at 25° C. up to 4.2 V. Then, they were discharged at a constant current of 0.1 C up to 3 V, and the initial charge capacity and the initial discharge capacity were measured. The results are shown in Table 2 below.

[0139] In addition, the positive electrode active materials prepared in Examples 1-2 and Comparative Examples 1-3, a conductive material (denka black), and a binder (PVDF) were mixed in a weight ratio of 97.5:1:1.5 in N-methyl-2-pyrrolidone (NMP) solvent to prepare positive electrode slurries. The positive electrode slurries were applied to one side of an aluminum current collector, dried, and then rolled to prepare positive electrodes.

[0140] Next, the negative electrode active material (natural graphite), the conductive material (carbon black), and the binder (PVDF) were mixed in a weight ratio of 95.6:1:3.4 in N-methyl-2-pyrrolidone (NMP) solvent to prepare a negative electrode slurry. The negative electrode slurry was applied to one side of a copper current collector, dried, and then rolled to prepare a negative electrode.

[0141] The electrode assembly was prepared by interposing a separator between the positive electrode and the negative electrode, and then placed in a battery case, and an electrolyte was injected to prepare a lithium secondary battery. The electrolyte was prepared by dissolving 1M LiPF6 in an organic solvent in which ethylene carbonate: ethyl methyl carbonate was mixed in a volume ratio of 3:7.

[0142] Then, the secondary batteries were charged to 4.2 V at a constant current of 0.1 C at 25° C. Then, they were discharged to 3 V at a constant current of 0.1 C (1 cycle), and then charged and discharged for 200 cycles in the range of 3 V to 4.2 V at a constant current of 0.33 C at 45° C. In this case, the discharge capacity at 200 cycles was divided by the discharge capacity at 1 cycle, and multiplied by 100 to calculate the capacity retention rate (%), which is shown in Table 2 below.

[0143] The secondary battery charged and discharged for one cycle and the secondary battery charged and discharged for 200 cycles were each perforated in a vacuum chamber to discharge the gas inside the battery and collect it inside the vacuum chamber, and the gas inside the chamber was quantitatively analyzed for the amount of gas generated using a gas chromatography-flame ionization detector (GC-FID).The amount of gas generated in the secondary battery charged and discharged for 200 cycles was then divided by the amount of gas generated in the secondary battery charged and discharged for one cycle, and multiplied by 100 to calculate the gas increase (%), which is shown in Table 2 below.

[0144] [Table 2]

[0145] As shown in Table 2, it can be seen that the capacity characteristics and gas generation reduction characteristics of the secondary batteries using the positive electrode active materials of Examples 1 and 2, in which the proportion of crystal grains C falls within the range of the present invention, are superior to those of the secondary batteries using the positive electrode active materials of Comparative Examples 1 to 3. It can also be seen that the life characteristics of the secondary batteries using the positive electrode active materials of Examples 1 and 2 are at the same level or higher than those of the secondary batteries using the positive electrode active materials of Comparative Examples 1 to 3.

Claims

1. a degree of crystal grain long axis orientation DoA represented by the following [Formula 1] is 0.5 to 1, and a proportion of crystal grains C having a degree of crystal grain c-axis orientation of less than 0.5 represented by the cross product value of a c-axis rotation vector Rc of a crystal lattice of the crystal grain and a position unit vector P' of the crystal grain, obtained by electron backscatter diffraction (EBSD) analysis, is 25% to 70% of all crystal grains in a cross section of a positive electrode active material particle, A positive electrode active material which is a lithium composite transition metal oxide represented by the following [Chemical Formula 1]: [Formula 1] [0010] In the formula 1, λ 1 is the long axis vector E of the crystal grain measured from image data obtained by analyzing the cross section of the positive electrode active material with a scanning ion microscope. I is the size of λ 2 is the short axis vector E of the crystal grain measured from image data obtained by analyzing the cross section of the positive electrode active material with a scanning ion microscope. II is the size of C D is the position unit vector P' and the major axis unit vector E of the grain I ' is the dot product value of [Chemical formula 1] Li x [Nia Co b M 1 c M 2 d ] O 2-y A y In the above [Chemical Formula 1], M 1 is one or more elements selected from the group consisting of Mn and Al; The M 2 is Nb; A is one or more elements selected from the group consisting of F, Cl, Br, I, At, and S; 0.98≦x≦1.20, 0<a<1, 0<b<1, 0<c<1, 0.00125≦d≦0.2, and 0≦y≦0.

2.

2. 2. The cathode active material according to claim 1, wherein the scanning ion microscope analysis includes irradiating a cross section of the cathode active material with a focused ion beam to obtain a scanning ion microscope image, and then using deep learning to obtain segmentation data for each crystal grain from the scanning ion microscope image, and calculating the DoA represented by [Equation 1] from the segmented data.

3. 2. The positive electrode active material according to claim 1, wherein the EBSD analysis is performed by obtaining EBSD Euler map data including position information and Euler angle information of each crystal grain through EBSD measurement of a cross section of the positive electrode active material, and calculating a c-axis rotation vector Rc(x, y, z) of a crystal lattice of the crystal grain according to the following Equation 2: [Formula 2] [0025] In the formula 2, [X, Y, Z] is (0, 0, 1), and ψ, θ, φ are Euler angles obtained from the Euler map data.

4. The positive electrode active material is The DoA is 0.5 to 1, and the crystal grain A has a crystal grain c-axis orientation degree of 0.5 to 1; Crystal grains B having a DoA of less than 0.5 and a crystal grain c-axis orientation degree of 0.5 to 1; The DoA is less than 0.5, and the crystal grain D has a crystal grain c-axis orientation degree of less than 0.5; 2. The cathode active material according to claim 1, wherein, of all the crystal grains in the cross section of the cathode active material particle, a ratio of crystal grains A is 20% or more and less than 25%, a ratio of crystal grains B is 5% to 30%, a ratio of crystal grains C is 25% to 70%, and a ratio of crystal grains D is 5% to 30%.

5. 5. The positive electrode active material according to claim 4, wherein the total ratio of crystal grains A and crystal grains C to all crystal grains in a cross section of the positive electrode active material particle is 50% to 90%.

6. The positive electrode active material according to claim 1, wherein the positive electrode active material has a crystal grain size of 70 nm to 200 nm.

7. The positive electrode active material according to claim 1 , wherein the positive electrode active material has a microstrain of 0.04% to 0.25%.

8. 2. The positive electrode active material according to claim 1, wherein the average particle size of the secondary particles of the positive electrode active material is 2 μm to 25 μm.

9. A positive electrode comprising the positive electrode active material according to any one of claims 1 to 8.

10. A lithium secondary battery comprising the positive electrode according to claim 9.

Citation Information

Patent Citations

  • Precursor for cathod active material of lithium secondary battery, cathode active materials made by the same, and lithium secondary battery containing the same

    KR101611784B1

  • Nickel manganese composite hydroxide and method for producing same, positive electrode active material for nonaqueous electrolyte secondary battery and method for producing same, and nonaqueous electrolyte secondary battery

    WO2018020845A1

  • Nickel manganese composite hydrhydroxide, production method for nickel manganese composite hydroxide, positive electrode active material for non-aqueous electrolyte secondary battery, production method for positive electrode active material for non-aqueous electrolyte secondary battery, and non-aqueous electrolyte secondary battery

    WO2018021555A1